Understanding perceptions of potato seed quality among small-scale farmers in Peruvian highlands. (1st March 2016) - Urrea-Hernandez, C.; Almekinders, C.J.M.; van Dam, Y.K.
Highlights: The study shows differences between expert and farmer perception of seed quality The results show that farmers have more integrated perception of seed quality The research methodology is a novel approach to study perception of seed quality Security, health and wellness are central values that drive farmer quality perception Abstract: The increased opportunities of smallholder farmers for commercial production of native potato varieties have resulted in an interest to support production and use of quality seed tubers of these varieties by the formal sector. In this context, a study was carried out to explore farmer perception of seed quality and the differences with formal expert perceptions of seed quality. It introduces Means-End-Chains methodology as a novel approach in studying farmers' decision on the use of varieties and seed. Results show that security, health and wellness are important personal values that influence the quality perception of small-scale farmers in Andean highlands. To pursue these values, they look for seed tubers that reflect the variety characteristics in combination with seed quality cues that reflect altitude, soil and low input management. Farmers do not associate these last ones with seed tubers from the formal seed sector.